THE FIRST FINDS OF ARMORED DINOSAURS IN THE UPPER CRETACEOUS OF RUSSIA (AMUR REGION) - Tumanova T.A.; Alifanov V.R.; Bolotsky Yu.L. (My University, 2004)
Remains of armored dinosaurs (Thyreophora) from the Late Cretaceous, Early Maastrichtian (Udurchukan Formation) deposits of the Kundur locality in the Amur Region, are described. The material includes a single osteodermal scute of extraordinary structure and two cheek teeth. These fossils are tentatively assigned to the family Nodosauridae (Ankylosauria) previously unknown in Asia.
Keywords: Armored dinosaurs; Upper Cretaceous; Russia; Amur Region; Mesozoic::Cretaceous; Мезозой::Меловая